2017
DOI: 10.12793/tcp.2017.25.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of skin permeation of vitamin C using vibrating microneedles

Abstract: This study was performed to evaluate the use of vibrating microneedles for the transdermal delivery of vitamin C. The microneedles were designed to vibrate at three levels of intensity. In vitro permeation by vitamin C was evaluated according to the specific conditions such as vibration intensity (levels 1, 2 and 3), application time (1, 3, 5, 7 and 10 min), and application power (500, 700 and 1,000 g). The highest permeation of vitamin C was observed at level 3 of vibration intensity, 5 min of application, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Vibrating microneedles have been used to apply a 1.5% AA gel [ 109 ]. The vibrating microneedles enhanced the permeation of AA through the excised abdominal skin of the rat, in a manner dependent on the vibration intensity, application power, and AA gel application time [ 109 ].…”
Section: Various Approaches To Maximize the Efficacy Of Aamentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrating microneedles have been used to apply a 1.5% AA gel [ 109 ]. The vibrating microneedles enhanced the permeation of AA through the excised abdominal skin of the rat, in a manner dependent on the vibration intensity, application power, and AA gel application time [ 109 ].…”
Section: Various Approaches To Maximize the Efficacy Of Aamentioning
confidence: 99%
“…Vibrating microneedles have been used to apply a 1.5% AA gel [ 109 ]. The vibrating microneedles enhanced the permeation of AA through the excised abdominal skin of the rat, in a manner dependent on the vibration intensity, application power, and AA gel application time [ 109 ]. Mesotherapy, a minimally invasive procedure involving a series of gentle, multiple micro-injections into the mesodermal layer under the skin, could be an additional option [ 110 , 111 ].…”
Section: Various Approaches To Maximize the Efficacy Of Aamentioning
confidence: 99%
“…Similarly, Badran et al found skin penetration and drug penetration to be enhanced by microneedling. In vitro and in vivo studies of vitamin C toxicity and efficiency administered in rats with vibrating microneedles (250 μm length) found a statistically significant increase in the permeability of active substances through the skin following treatment …”
Section: Discussionmentioning
confidence: 98%
“…In a study investigating the in vitro and in vivo effectiveness of vibrating microneedles the on transdermal delivery of vitamin C, the microneedles were administered at three different intensity levels (level 1, 2 and 3), five different application times (1, 3, 5, 7, and 10 minutes) and three different application powers (500, 700 and 1000g). Obtained findings of both studies exhibited that vibrating microneedles significantly increased the permeability of Vitamin C from the skin resulting in enhanced AUC0-∞ and Cmax in rats [30]. Moreover, Liu et al performed a study to investigate the effect of vibration on transdermal delivery of insulin.…”
Section: Discussionmentioning
confidence: 99%